A Comparison between Literature Findings and Stakeholder Perspectives on Active Travel Promotion. (June 2017) - de Nazelle, Audrey; Smeds, Emilia; Anaya Boig, Esther; Wang, Chao; Sanchez, Julian; Dons, Evi; Kahlmeier, Sonja; Iacorossi, Francesco; Wegener, Sandra; Nieuwenhuijsen, Mark; Rojas-Rueda, David; Avila-Palencia, Ione; et al.
Abstract : Background: Cities are increasingly turning towards active travel policies to help address some the world's greatest public health challenges, in particular physical inactivity. However, what will actually work to promote walking and cycling remains uncertain, and findings from the scientific literature may differ from what stakeholders and decision makers believe. Comparing these perspectives can help better align science and policy making. Methods: Drawing on research conducted as part of the PASTA (Physical Activity through Sustainable Transport Approaches) project, this study compares the perspectives of stakeholders on active transport with academic evidence, with regard to 1) barriers to active travel behaviour, and 2) policy measures effective in promoting active transport. In 7 case-study cities across Europe, stakeholder perspectives were investigated by means of semi-structured interviews and workshops involving a total of 59 stakeholders representing health, environment, transport and planning sectors. These perspectives are compared to findings from a review of reviews in the literature. Results: There is a good degree of alignment on the relevance of infrastructure measures such as cycle lanes, bike sharing, and creating attractive routes; social environment measures such as awareness campaigns and travel to school campaigns; and regulatory measures such as pedestrian friendly zones and car parking restrictions. The literature seems to put more emphasis on the use of cycle subsidies and training, traffic calming and temporary road closures, while stakeholders lay more hope on increasing cycle parking than the literature warrants. The literature highlights the effectiveness of approaches such as showers at work, signage, individual marketing, and car free zones which are not mentioned in general by stakeholders. In reverse the quality of infrastructure, cycling maps, low emissions zones, highway codes and 30km/h zones are only highlighted by stakeholders. Conclusions: The study identifies areas which could benefit from better research translation, or in reverse, where research gaps may exist. There are challenges in interpreting such comparisons, such as issues with language or terminology used in different sectors, with framework and implementation conditions which may affect stakeholders' perception on feasibility, and with the difficulty of evaluating complex measures. The study proposes a novel approach to help better align research and policy research which should be further explored in the future with more targeted stakeholder interview protocols.